An ultra-low power ECG acquisition and monitoring ASIC system for WBAN applications - Endru, F. N. (2013)
This paper proposes a power and area efficient electrocardiogram (ECG) acquisition and signal processing application sensor node for wireless body area networks (WBAN). This sensor node can accurately record and detect the QRS peaks of ECG waveform with high-frequency noise suppression. The proposed system is implemented in 0.18-μm complementary metal-oxide-semiconductor technology with two chips: analog front end integrated circuit (IC) and digital application specific integrated circuit (ASIC), where the analog IC consumes only 79.6 μW with area of 4.25 mm2 and digital ASIC consumes 9 μW at 32 kHz with 1.2 mm2. Therefore, this ECG sensor node is convenient for long-term monitoring of cardiovascular condition of patients, and is very suitable for on-body WBAN applications.